2008
DOI: 10.1152/ajpcell.16.2008
|View full text |Cite
|
Sign up to set email alerts
|

Early mechanical dysfunction of the diaphragm in the muscular dystrophy with myositis (Ttnmdm) model

Abstract: A complex rearrangement mutation in the mouse titin gene leads to an in-frame 83-amino acid deletion in the N2A region of titin. Autosomal recessive inheritance of the titin muscular dystrophy with myositis (Ttn(mdm/mdm)) mutation leads to a severe early-onset muscular dystrophy and premature death. We hypothesized that the N2A deletion would negatively impact the force-generating capacity and passive mechanical properties of the mdm diaphragm. We measured in vitro active isometric contractile and passive leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(89 citation statements)
references
References 35 publications
15
74
0
Order By: Relevance
“…Passive stiffness and passive tension are higher in mutant muscle than in wild-type muscle for whole-muscle experiments (Lopez et al, 2008), although Witt et al (2004) did not observe differences in passive tension in single muscle fibers. Higher passive stiffness could result from the presence of more collagen and/or from a shorter titin spring (Lopez et al, 2008). An increase in muscle stiffness should result in an increase in tremor frequency for mdm mutants, not a decrease in tremor frequency, as we observed.…”
Section: Mass and Stiffness Modelmentioning
confidence: 77%
See 4 more Smart Citations
“…Passive stiffness and passive tension are higher in mutant muscle than in wild-type muscle for whole-muscle experiments (Lopez et al, 2008), although Witt et al (2004) did not observe differences in passive tension in single muscle fibers. Higher passive stiffness could result from the presence of more collagen and/or from a shorter titin spring (Lopez et al, 2008). An increase in muscle stiffness should result in an increase in tremor frequency for mdm mutants, not a decrease in tremor frequency, as we observed.…”
Section: Mass and Stiffness Modelmentioning
confidence: 77%
“…Although Lopez et al (2008) found a higher slow:fast ratio for the myosin heavy chain isoform in mutant muscle than in non-mutant control muscles, these authors reported that mutant muscle actually had a shorter time to peak force and a shorter half-relaxation time compared with non-mutant controls. Therefore, if tremor frequency were dependent on muscle contraction kinetics, we would expect that mutants would shiver at or above expected tremor frequencies, not below, as we observed.…”
Section: Mass and Stiffness Modelmentioning
confidence: 87%
See 3 more Smart Citations